Epidemiology of Schistosomiasis in Two High-Risk Communities of South Côte d'Ivoire with Particular Emphasis on Pre-School–Aged Children - Coulibaly, Jean T. (The American Society of Tropical Medicine and Hygiene, 2013)
Schistosomiasis control efforts mainly target school–aged children. We studied the epidemiology of schistosomiasis in two high-risk communities in south Côte d'Ivoire, placing particular emphasis on pre-school–aged children. We used a suite of diagnostic techniques, including Kato–Katz, urine filtration, reagent strips, and urine circulating cathodic antigen cassettes. Risk factors for schistosomiasis were determined by focus group discussions and a structured questionnaire. The prevalence of Schistosoma mansoni in the two study villages among the pre-school–aged children (age < 6 years) was 20.9% and 25.0%, whereas several-fold higher prevalences were found in school–aged children (58.7–68.4%) and adolescents/adults (59.5–61.7%). The prevalence of S. haematobium in the three age groups was 5.9–17.3%, 10.9–18.4%, and 3.8–21.3%, respectively. Most participants had light-intensity infections. Mothers' occupations and older siblings play important roles in the epidemiology of schistosomiasis in pre-schoolers. In the current epidemiologic settings, more attention is warranted on pre-school–aged children and adolescents/adults for successful schistosomiasis control.